From State to Public Service: Legal and Structural Constraints in the Sri Lankan Broadcasting Sphere - Weerasinghe, Pradeep Nishantha (UIR Press, 2023)
In the contemporary world, Public Service Broadcasting plays a decisive and challenging role in creating an informed citizenry through editorial independence, diversity of content, freedom of expression, audience participation, and active democracy. However, in Sri Lanka, the opposite is true, where there are no public service media, but state-owned and privately-owned media enterprises. This paper looks at the absence of public service broadcasting in Sri Lanka, its effect on a democratic society, and its resistance to the initiative. The case study desk review approach was employed to investigate public service broadcasting in the Sri Lankan context. The study finds that in the absence of public service media, citizens tend to consume information reproduced and delivered through a hegemonic media landscape, compiled according to the agenda of radio and television station owners. Such content has been found to be devoid of professionalism, editorial independence, diversity, and pluralism, leading to misrepresentation of facts in the coverage of conflicts, controversial issues, and elections, and by extension the destruction of society. In Sri Lanka, a developing country, state-owned media must be transformed into public service media. The selfish interests of political parties, policymakers, bureaucracy, and trade unions and limited awareness amongst the public makes this task difficult. The study recommended to appoint a public commission to identify processes and actions to transform State owned media to public service media. Nevertheless, suggests to launch a public campaign that would educate the public and influence policy makers’ thinking towards liberating State owned media from government control.